ANALISIS FINANSIAL PEMANENAN KAYU TEKNIK REDUCED IMPACT LOGGING MELALUI SKEMA REDD+, KALIMANTAN UTARA - Muhdi; Juang Rata Matangaran (Talenta Publisher, 2015)
The research was done at a natural tropical forest of PT Inhutani II, East Kalimantan. The objectivesof the research were to study the carbon (C) stock in the natural tropical forest after conventional andreduced impact logging (RIL) and to get the effectivity of RIL based on carbon stock, financial andenvironmental aspects. The effect of conventional and RIL on the environment and carbon stock in theplots was studied using the data of three plots with each size 100 m x 100 m. The plots are placedbased on purposive sampling at landing, main skid trail, and branch skid trails, respectively. Cstocks are counted by allometric equations and C economics by the economic acceptance of REDD.Economic value of RIL was IDR 1,604,518,900,- ha-1. Based on financial analysis showed that RILwas feasible and profitable at a rate of interest 16 %.